Facile pretreatment strategies to biotransform Kans grass into nanocatalyst, cellulolytic enzymes, and fermentable sugars towards sustainable biorefinery applications - Singh P.; Srivastava N.; Mohammad A.; Lal B.; Singh R.; Syed A.; Elgorban A.M.; Verma M.; Mishra P.K.; Gupta V.K. (My University, 2025)
The present investigation is targeted towards the facile fabrication of a carbon-based nanocatalyst (CNCs) using Kans grass biomass (KGB) and its sustainable application in microbial cellulase enhancement for the alleviation of enzymatic hydrolysis for sugar production. Different pretreatments, including physical, KGB extract-mediated treatment, followed by KOH pretreatment, have been applied to produce CNCs using KGB. The presence of CNCs influences the pretreatment of KGB substrate, fungal cellulase production, stability, and sugar recovery in the enzymatic hydrolysis of KGB. Using 1.0% CNCs pretreated KGB-based solid-state fermentation, 33 U/gds FPA and 126 U/gds BGL were obtained at 72 h, followed by 107 U/gds EG at 48 h in the presence of 0.5% CNCs. Further, 42 °C has been identified as the optimum temperature for cellulase production, while the enzyme showed thermal stability at 50 °C up to 20 h and produced 38.4 g/L sugar in 24 h through enzymatic hydrolysis of KGB. © 2023 Elsevier Ltd